Contrastive Analysis Between English And Indonesian Quotes In The Utterances Of The Character In The Movie " Doctor Strange 2 Multiverse Of Madness" - Kosasih Galingging, Cikep; Tannuary, Arwin (Journal of Social Science and Humanities Research, 2022)
Doctor Strange in the Multiverse of Madness (2022) was written by Michael Waldron and Directed by Sam Raimi based on Marvel Comics and produced by Kevin Feige. Using descriptive qualitative method his study entitled “Contrastive Analysis between English and Indonesian Quotes in The Utterances of the Character in the movie " Doctor Strange 2 Multiverse of madness" aims to understand the meaning of quotes based on the translation of the film's subtitle. English and Indonesian quotes themselves have different meanings. With the Contrastive aspect of analysis which is based on finding the difference in meaning between English and Indonesian. The results of the analysis are used to broaden the horizons in understanding meaning by using translation techniques by juxtaposing meaning using the Contrastive aspect of analysis. Therefore, several translation techniques are used as a comparison medium such as literal translation, borrowing, and calque.